Investigating the impact of credit risk on financial performance of commercial banks in Ghana - Angela Akpemada Kwashie; Samuel Tawiah Baidoo; Enock Kojo Ayesu (Cogent Economics & Finance, 2022)
The financial performance of banks across the globe is of utmost importance to its shareholders, managers, investors, regulators, and the general public. This study therefore investigates the impact of credit risk with focus on non-performing loans on the financial performance of commercial banks in Ghana. Return on asset and economic value-added are used as measures of financial performance. Internal bank factors such as the age and size of the bank are also considered. Macroeconomic factors such as gross domestic product, inflation, and monetary policy rate are included in the analysis. Panel data spanning the period 2013 to 2018 on 15 commercial banks in Ghana is used for the analysis. The results from the random effect estimation technique show that non-performing loans have a negative impact on both measures of financial performance. Also, monetary policy rate has a negative impact on both measures of financial performance, albeit insignificant for economic value-added measure. It is further revealed that the size of bank, age of bank, and gross domestic product have a significant positive effect on both measures of financial performance although significant for return on asset. Based on the negative relationship between non-performing loans and financial performance, it is suggested that commercial banks should adopt stringent credit risk management policies, which should also be updated regularly to guide actions and processes to granting of loans and monitoring credit risk. Furthermore, it is suggested that the value of depreciable assets pledged as collaterals to the banks should be reviewed frequently (probably annually) to reflect a decline in their value. The novelty of the present study pertains to the use of economic value-added as a financial performance measure, which previous studies have virtually ignored in the analysis of credit risk and financial performance nexus.
Keywords: 330; Credit risk; financial performance; non-performing loans; economic valueadded; Ghana